Implicit theories of leadership malleability: How beliefs about the malleability of leadership characteristics predict employee voice - Ziyi Zhang; Michael P. Haselhuhn (PLoS ONE, 2026)
Despite the proliferation of research emphasizing the importance of growth mindsets in a wide range of domains, research examining these mindsets in the context of leadership has been overlooked. This research expands implicit theories to the leadership discipline and explores how beliefs about the fixedness or malleability of leadership characteristics (termed Implicit Theories of Leadership Malleability; ITLMs ) affect employee voice. Through four studies, findings suggest that beliefs in the malleability of leadership characteristics predict employees’ voice behaviors in the workplace, and that this link is mediated by the perceived efficacy of voice. The relationship between ITLMs and voice is stronger when voice is directed toward growth and improvement (i.e., promotive voice) relative to voice directed toward avoiding failure (i.e., prohibitive voice).